The meaning of confidence for older people living with frailty: A qualitative systematic review - Underwood, F.; Burrows, L.; Gegg, R.; Latour, Jos; Kent, B. (University of Adelaide * Faculty of Health Sciences, 2017)
© 2017 THE JOANNA BRIGGS INSTITUTE. EXECUTIVE SUMMARYBackground In many countries, the oldest old (those aged 85 years and older) are now the fastest growing proportion of the total population. This oldest population will increasingly be living with the clinical condition of frailty. Frailty syndromes negatively impact on the person as they do the healthcare systems supporting them. Within healthcare literature "loss of confidence" is occasionally connected to older people living with frailty, but ambiguously described. Understanding the concept of confidence within the context of frailty could inform interventions to meet this growing challenge. Objectives The objective of this systematic review was to explore the meaning of confidence from the perspective of older people living with frailty through synthesis of qualitative evidence to inform healthcare practice, research and policy. Inclusion criteria Types of participants Studies that included frail adults, aged over 60 years, experiencing acute hospital and or post-acute care in the last 12 months. Phenomena of interest The concept of "confidence" and its impact on the physical health and mental well-being of older people living with frailty. Context Studies that reported on the older person's descriptions, understanding and meaning of confidence in relation to their frailty or recent healthcare experiences. Types of studies Studies of qualitative design and method. Search strategy A three step search strategy was used. The search strategy explored published studies and gray literature. Publications in English from the last 20 years were considered for inclusion. Methodological quality All included articles were assessed by two independent reviewers using the Joanna Briggs Institute Qualitative Assessment Review Instrument (JBI-QARI). Data extraction Data were extracted from included studies using the data extraction tools developed by the Joanna Briggs Institute. Data synthesis Qualitative research findings were collated using a meta-aggregative approach and JBI-QARI software. Results Synthesized findings of this review were drawn from just four research studies that met the inclusion criteria. Only six findings contributed to the creation of three categories. These informed a single synthesized finding: Vulnerability, described as a fragile state of well-being that is exposed to the conflicting tensions between physical, emotional and social factors. These tensions have the capability to enhance or Erode this state. Conclusions Assertions that an understanding of the concept confidence has been reached cannot be made. The review data offer limited insight into the concept of confidence being described by the cohort of older people living with frailty.